2000
DOI: 10.1096/fasebj.14.2.301
|View full text |Cite
|
Sign up to set email alerts
|

An oncolytic herpes simplex virus type 1 selectively destroys diffuse liver metastases from colon carcinoma

Abstract: Viruses used for gene therapy are usually genetically modified to deliver therapeutic transgenes and prevent viral replication. In contrast, replication-competent viruses may be used for cancer therapy because replication of some viruses within cancer cells can result in their destruction (oncolysis). Viral ribonucleotide reductase expression is defective in the HSV1 mutant hrR3. Cellular ribonucleotide reductase, which is scarce in normal liver and abundant in liver metastases, can substitute for its viral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 32 publications
1
89
0
1
Order By: Relevance
“…BALB/c mice weighing [15][16][17][18][19][20] into the spleens of BALB/c mice. Animals were treated three days later with a single intrasplenic administration of either 5 ϫ 10 7 pfu rRp450 or mock-infected control media.…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…BALB/c mice weighing [15][16][17][18][19][20] into the spleens of BALB/c mice. Animals were treated three days later with a single intrasplenic administration of either 5 ϫ 10 7 pfu rRp450 or mock-infected control media.…”
Section: Animal Studiesmentioning
confidence: 99%
“…16,21 To examine the therapeutic potential of rRp450 against diffuse colon carcinoma liver metastases, MC26 liver metastases were established in BALB/c mice, and the mice were subsequently treated with a single intraportal inoculation of mock-infected media or 5 ϫ 10 6 pfu rRp450 three days later. Mice were randomized to receive a single intraperitoneal injection of either PBS or cyclophosphamide (30 mg/kg) two days following virus administration.…”
Section: Rrp450 Effectively Treats Diffuse Colon Carcinoma Liver Metamentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effect of rHSV is reported to be much greater than its evident distribution throughout tumors (20)(21)(22)(23)(24)(25). HSV infection induces apoptosis in adjacent, uninfected cells in vitro and in vivo (26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, viral delivery to tumor confined within an anatomical compartment, such as the peritoneal cavity, pleural cavity, or the bladder, also exhibits significant antitumoral effects (19 -21). Studies have also shown that selective intra- portal or intrasplenic delivery of an oncolytic virus may effectively treat animal models of liver tumors (22,23). The potential of these agents to treat regionally metastatic nodal disease has also been demonstrated previously (24).…”
Section: Discussionmentioning
confidence: 99%